Sustainable agricultural intensification practices and rural food security: The case of Northwestern Ghana. Issue 2 (5th February 2018) - Yahaya, Iddrisu; Pokharel, Krishna P.; Alidu, Abdul-Fatahi; Yamoah, Fred Amofa
Abstract : Purpose: The purpose of this paper is to understand the impact of participation in sustainable agricultural intensification practices (SAIPs) on household food security status in Northwestern Ghana. Design/methodology/approach: The study utilised the Household Food Insecurity Access Scale (HFIAS) indicator for the measurement of food access data from 168 households in ten communities from the Northwestern region of Ghana for the analyses. Households were categorised into participating households (treatment) and non-participating households (control). The endogenous treatment effects model was employed to evaluate the impact of participation in SAIPs training on food insecurity access scale. Findings: The results show that participation in SAIPs training lowers, on average, the household food insecurity access by 2.95 points, approximately an 11 per cent reduction in HFIAS score. Other significant factors found to influence household food insecurity access scale are age of household head, experience in farming, total acres owned by household, income level of the household and occupation of the head of the household. Research limitations/implications: The training programme of participation in SAIPs has massive implications for food security, rural economy and farmers' livelihoods. However, due to the unique conditions prevailing in Northwestern Ghana, the findings of this research are limited in terms of their generalisability. Future research direction in the area of SAIPs trainings and impact study replications in all qualifying rural food production areas in Ghana, which are susceptible to household food insecurity, will provide a national picture of the efficacy of SAIPs trainings on household food insecurity. Practical implications: A proven means to decrease natural resource degradation, increase crops yields, and increase subsistence farmers' income, and food security is an important intervention to resolve the seasonal food shortage, which last for five months in a typical year for agro-food-dependent farming communities in Northwestern Ghana. Social implications: Ensuring household food security improvement and environmental sustainability will help improve living standards of food producers and reduce the adverse social challenges associated with food insecure communities such as health problems due to food deficiencies, social inequalities, environmental pollution and natural resource degradation in Northwestern Ghana. Originality/value: The contribution of this paper is the novel thought and approach to examine the impact of the SAIPs trainings on household food security in Northwestern Ghana using the household food insecurity access scale indicator. The study also examined the factors that affect household food security using the endogenous treatment model, which also evaluates the impact of the training programme on the outcome variable.